Organophosphites: an addition to the arsenal of organocatalysts - Baral, Nilofar; Rani, Soniya; Saikia, Pinku; Maity, Pradip (European Journal of Organic Chemistry, 2023)
Organophosphites are nucleophilic in nature and can act as a good leaving group owing to the stability of the phosphite anion. This dual reactivity makes them good candidates for nucleophilic organocatalysis. However, phosphites were introduced only in 2004 as the umpolung catalyst for acylsilane substrates utilizing sequential Brook rearrangements. Very recently, phosphites have been reported to catalyze aza-rearrangements and radical reactions. In this review, we discuss the reactivity parameters to understand its lack of use, as well as the potential for catalysis.
Keywords: acylradical; azaacyl equivalent; cylanion; organocatalysis; phosphite